Inoculation with rhizobacterial consortia alleviates combined water and phosphorus deficit stress in intercropped faba bean and wheat - Cheto, Said; Oukaltouma, Khawla; Chamkhi, Imane; Ibn Yasser, Ammar; Benmrid, Bouchra; Qaddoury, Ahmed; Kouisni, Lamfeddal; Geistlinger, Joerg; Zeroual, Youssef; Bargaz, Adnane; Ghoulam, Cherki (Frontiers in Sustainable Food Systems, 2023)
Our study aimed to assess the role of inoculation of faba bean/wheat intercrops with selected rhizobacterial consortia (composed of one rhizobium and two P solubilizing bacteria “PSB”) to alleviate the effects of combined water deficit and P limitation on faba bean/wheat intercropping vs. monocropping under greenhouse conditions. One Vicia faba L (Aguadulce) and one Triticum durum L. variety (Karim) were grown as a sole crop or were intercropped in pots containing a sterilized substrate (sand:peat 4:1 v/v) with either rock phosphate (RP) (unavailable P) or KH2PO4 in the nutrient solution (available P). Plant inoculation was performed using the rhizobacterial consortia C1 (Rhizobium laguerreae, Kocuria sp., and Pseudomonas sp.) and C2 (R. laguerreae, Rahnella sp., and Kocuria sp.). Two weeks after inoculation, the plants were subjected to water deficit with 40% substrate water holding capacity (WHC) vs. 80% WHC for the well-watered plants. The trial was assessed at the flowering stage, and the results showed that inoculation with both consortia (C1 and C2) improved faba bean biomass in terms of shoot, root, and nodules dry weight compared to inoculation with rhizobia alone. C2 improved these parameters by 19.03, 78.99, and 72.73%, respectively. The relative leaf water content decreased under combined stress, especially in response to C1 conferring significant improvement of this parameter in wheat intercrops. In faba bean under P limitation, inoculation with C2 increased stomatal conductance (gs), phosphatase, and phytase activity by 35.73, 166.94, and 26.16%, respectively, compared to plants inoculated with rhizobia alone. Furthermore, C2 also improved membrane stability under P deficit by 44.33 vs. 16.16% for C1 as compared to inoculation with rhizobia alone. In sole-cropped faba bean, inoculation with both consortia improved N accumulation compared to single inoculation with an increase of 70.75% under P limitation. Moreover, under combined stress, inoculation with C2 improved biomass and N content (112.98%) in intercropped wheat compared to the sole crop. Our findings revealed that consortium C2 might offer an agronomic advantage under water and P deficit and could serve as a useful inoculum for enhancing faba bean and wheat production in monocropping and intercropping systems.